2019
DOI: 10.1021/acs.jafc.9b03780
|View full text |Cite
|
Sign up to set email alerts
|

Role of Characteristic Components of Humulus lupulus in Promoting Human Health

Abstract: Over the next 50 years, the prevention and control of chronic diseases, such as obesity, cardiovascular disease, Alzheimer's disease, and many cancers, will be one of the most critical challenges in human health. Plant biochemistry and phytonutrient supplements are a promising complementary therapy for the management of chronic disease. Among them, Humulus lupulus has attracted special attention throughout the world because it contains numerous dietary phytochemicals that not only contribute to the aroma and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 71 publications
(134 reference statements)
0
35
0
4
Order By: Relevance
“…Recently, accumulating evidence indicates that xanthohumol possesses the potent anti-cancer efficacy in various tumor models, such as hepatocellular carcinoma, leukemia, melanoma, non-small cell lung cancer, colorectal, ovarian, pancreatic, and cervical cancer (46). Mechanism study revealed that induction of cell cycle arrest, inhibition of glycolysis, promotion of DNA damage and apoptosis, and suppression of angiogenesis/metastasis are contributed to the anti-tumor activity of xanthohumol (46)(47)(48). Beyond that, the combination of xanthohumol with other therapeutic agents enhanced the tumor-killing effect of chemotherapy in various tumor models (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating evidence indicates that xanthohumol possesses the potent anti-cancer efficacy in various tumor models, such as hepatocellular carcinoma, leukemia, melanoma, non-small cell lung cancer, colorectal, ovarian, pancreatic, and cervical cancer (46). Mechanism study revealed that induction of cell cycle arrest, inhibition of glycolysis, promotion of DNA damage and apoptosis, and suppression of angiogenesis/metastasis are contributed to the anti-tumor activity of xanthohumol (46)(47)(48). Beyond that, the combination of xanthohumol with other therapeutic agents enhanced the tumor-killing effect of chemotherapy in various tumor models (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…In traditional medicine, hops have long been used to treat sleep disorders, as a stomach remedy, and as an antibacterial and antifungal agent [ 3 ]. Humulus lupulus attracted special attention because it contains many dietary phytochemicals that can be used for medicinal purposes, due to their antiseptic, (an)aphrodisiac, anticancer, antiplatelet, antidiuretic, antiinflammatory and sedative properties [ 4 ].…”
Section: Hopmentioning
confidence: 99%
“…▶ Table 3 Percentage of prenylated hops compounds (1)(2)(3)(4)(5) in investigated samples (Prod1-6) (n = 3) determined via quantitation using the PDA signal at 220 nm. The calculated recommended daily intake of reference substances in μg per dietary product (Prod1-4) is given in parentheses.…”
Section: Standards Samples and Solventsmentioning
confidence: 99%
“…The flowers (also called cones or hop strobile) of Humulus lupulus L. (Cannabaceae) are not only used for adding aroma and bitterness to beer, but also for their health benefits. Therefore, hop is of interest for both the food and pharmaceutical industry [1]. In 2016, the Committee on Herbal Medicinal Products concluded that on the basis of its long-standing use, hop strobile preparations can be used for mild symptoms of mental stress and to aid sleep (EMA/304 459/2016) [2].…”
Section: Introductionmentioning
confidence: 99%